Strain partitioning in the Variscan deformation of the Marão domain (Central Iberian zone; northern Portugal) - Dias, Rui (2022)
formation of the Ibero-Armorican Arc, a major structure in the SW Variscan orogeny, induced in most of its southern Iberian branch a heterogeneous sinistral transpressive regime. The presence of pre- and syn-orogenic steep planar anisotropies subparallel to the main WNW-ESE structural trend, gave rise to an important strain partitioning of the Variscan deformation. This lead to the lateral juxtaposition of narrow blocks where simple shear dominated transpression predominates, with wider ones where the pure shear to pure shear dominated transpression is pervasive. This partitioning of deformation is observed from the orogenic macroscale to the mesoscopic and even microscopic scales. The detailed structural mapping of the well exposed Lower Ordovician Armorican quartzites in one of the simple shear dominated sectors (the Mar˜ao Mountain in Northern Portugal), coupled with microstructural observations of chosen thin sections, emphasize the coeval development of WNW-ESE sinistral shear zones and subparallel folds. The interference between different Variscan structures, with particular geometries and kinematics, help to understand how transpressive regimes related to the major early oblique orogenic collisions could evolve to late intracontinental orthogonal collision. When the Variscan transpressive regime of Mar˜ao is interpreted in the context of the Iberian Variscides, it becomes clear that independent sectors of the same fold belt could compensate the orogenic shortening by different amounts of vertical thickening versus horizontal lateral escape. This explains why tectonic domains where the structures are related with a stretching subparallel to the a kinematic axis (X ≡ akin), could exist in the vicinity of domains where the stretching is subparallel to the b kinematic axis (X ≡ bkin).